Les tribulations parisiennes de l’officier écrivain : l’oeuvre autobiographique de Yasmina Khadra et son accueil en France - Pawlicki, Jędrzej (Studia Romanica Posnaniensia, 2012)
This article describes Yasmina Khadra’s autobiographical work composed of two books: "L’écrivain" and "L’imposture des mots" and its reception in France. The main purpose of this study was to establish the literary genre of these books, which implies determining whether Khandra’s work represents an autobiography or an autofiction with reference to P. Lejeune’s and V. Colonna’s theoretical studies. The dividing line between two genres in Khandra’s works reflects his inner split between being either a solder or a writer. The presentation will also help to understand the controversy resulting from Khandra’s participation in Algerian civil war. Moreover the analysis is related to modern Algerian history.